Phonetic Analysis of Isymam in Qiraat Imam 'Ashim: A Study of Ashwat Science in Grade 10 Students of Sma It Al-Huda Cianjur - Habiburahman; Lina Marlina (Penerbit Hellow Pustaka, 2026)
This research is motivated by the still low level of students' understanding and mastery of the phonetic phenomenon of isymam in the recitation (qiraat) of Imam ‘Asim, particularly in terms of pronunciation. Isymam is one of the rare forms of recitation (qiraat gharīb) that holds significance in the science of Qur’anic recitation and possesses distinct phonetic characteristics that are not represented in writing but are only found in oral practice. The aim of this study is to analyze students’ ability to pronounce isymam in the recitation of Imam ‘Asim, as well as to examine the factors causing pronunciation errors. This is a field study using a qualitative approach. Data were collected through observation, interviews, and oral tests of Qur’anic reading. The data analysis technique employed is a descriptive-evaluative method, and the results are presented narratively. The findings show that a small number of students still struggle to accurately demonstrate the pronunciation of isymam, mainly because it requires coordination between producing the dammah vowel sound and a simultaneous but voiceless lip movement. Contributing factors to the mispronunciation include limited practice-based qiraat learning in madrasahs, the lack of phonetic Qur’an training, and the absence of dedicated programs for the rare recitations of Imam ‘Asim. Therefore, a phonetic-based approach and intensive training are needed to enhance students' proficiency in reading the Qur’an more fluently in accordance with authentic qiraat rules.